Uveitis: Molecular Pathogenesis and Emerging Therapies - Egwuagu, Charles E.; Alhakeem, Sahar A.; Mbanefo, Evaristus C. (Frontiers in Immunology, 2021)
The profound impact that vision loss has on human activities and quality of life necessitates understanding the etiology of potentially blinding diseases and their clinical management. The unique anatomic features of the eye and its sequestration from peripheral immune system also provides a framework for studying other diseases in immune privileged sites and validating basic immunological principles. Thus, early studies of intraocular inflammatory diseases (uveitis) were at the forefront of research on organ transplantation. These studies laid the groundwork for foundational discoveries on how immune system distinguishes self from non-self and established current concepts of acquired immune tolerance and autoimmunity. Our charge in this review is to examine how advances in molecular cell biology and immunology over the past 3 decades have contributed to the understanding of mechanisms that underlie immunopathogenesis of uveitis. Particular emphasis is on how advances in biotechnology have been leveraged in developing biologics and cell-based immunotherapies for uveitis and other neuroinflammatory diseases.